Recent Trends in Catalysis for Syngas Production and Conversion - Meng, Fanhui; Mo, Wenlong (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Syngas (CO and H2) is a crucial platform for the production of a variety of high-value compounds. This reprint focused on research into the production of syngas, the conversion and application of syngas, and catalyst synthesis.